The Role of Tuan Guru on Improving Iron Intake and Minimalizing Food Restriction Behavior among Pregnant Women with Anemia - Sabi'ah Khairi; Lalu Muhammad Harmain Siswanto; Heri Bahtiar; Ristrini Ristrini (Pediomaternal Nursing Journal, 2021)
Introduction: Anemia in pregnancy is an indirect cause maternal mortality. One of causes anemia during pregnancy is deficit of nutrient especially intake of iron. The aim of this study was to know that the role of religious leaders that called “Tuan Guru” as agent of change to improving iron intake among anemia pregnant women.Methods: This study was quasi-experimental with pre and post-test group design. 86 participants pregnant women with anemia have been recruited in this study with purposive sampling technic. They were divided in intervention group (47 participants) and control group (39 participants). This study involved Tuan Guru as main intervention to give health promotion about nutrition during pregnancy. This study used food recall as an instrument tool that it used to measure nutrient intake especially intake of iron both pre and post intervention and also used questonare to measure food restriction behaviour among anemia pregnant women. Statistical test used paired t-testResults: This study show that there were effect of religious leaders to improving the iron intake among pregnant women with anemia with p=0.01. This study also found that the habits of food restriction among pregnant women are decline between before and after intervention with p=0.00.Conclusion: Tuan Guru has a strong influence in helping to increase nutritional intake and is able to minimize the food restriction behaviour among anemia pregnant women. The result of this study can be a basis for government to make a policy related to involvement of religious leaders in health promotion.